DOPING KNOWLEDGE AND PRACTICE AMONG ELITE ATHLETES IN TERTIARY INSTITUTIONS IN NIGERIA - I. O. Akindutire; J. A. Adegboyega; J. A. Olanipekun (European Scientific Journal, ESJ, 2012)
This study investigated doping knowledge and practice among the elite athletes in tertiary institutions in Nigeria. Also, it examined the extent to which athletes in tertiary institutions have actually used doping substances. A total of 510 athletes (255 males and 255 females) were randomly sampled from tertiary institutions in three states (Ekiti, Ondo and Oyo States). A structured questionnaire designed by the researchers was used to collect relevant data for the study. The data collected were analysed using descriptive statistics, Chi-square (X2) test and Analysis of variance (ANOVA). The results showed that athletes in tertiary institutions were aware of doping substances used in sports. The athletes had tried doping substances such as methadone, cocaine, phenobarbital, stanozolol, nandrolone decanoate and caffeine. The study revealed that more male than female athletes engaged in doping practices. Also, the type of sports participated by the athletes influenced their doping habits. It was therefore recommended that the Nigerian Government should intensify its campaign and public enlightenment programmes to educate the athletes and sports handlers on the health consequences of doping to enhance sports performance. Also, the Government should make funds, facilities and personnel available for a forensic laboratory for drug testing.